THE ROLE AND ROLE OF MULTIMEDIA TECHNOLOGY IN LITERATURE TEACHING (Academicia Globe: Inderscience Research, 2024)
This article details the changing impact of multimedia technology on teaching literature, its ability to strengthen understanding, develop creativity and expand the horizons of learning, interactive simulations, multimedia tools provide students with dynamic and interesting learning experience outside traditional textbook-based teaching restrictions, the use of multimedia technology and the development of digital literacy skills.